Association of self-reported sleep duration with leukocyte telomere length in type 2 diabetes mellitus patients - Wang, Liqun; Pan, Ruiping; Yan, Ning; Luo, Yiling; Wang, Yali (Frontiers in Endocrinology, 2025)
BackgroundLeukocyte telomere length (LTL) is a biomarker of aging, and sleep duration is associated with LTL. However, research exploring the relationship between sleep duration and LTL has yielded inconsistent results. This study aimed to investigate the association between sleep duration and LTL in Chinese patients with type 2 diabetes mellitus (T2DM).MethodsA cross-sectional study involving 1,027 T2DM patients was conducted in Ningxia Province, China. Sleep duration was assessed through self-reported measures, while leukocyte telomere length (LTL) was determined using a quantitative polymerase chain reaction (q-PCR) method. Restricted cubic splines (RCS) analysis was initially performed to evaluate the potential nonlinear relationship between sleep duration and LTL. Subsequently, a multiple mixed-effect linear regression model was utilized to examine this association.ResultsBinary analysis revealed an inverse association between sleep duration and LTL (β=-0.170, 95%CI: (-0.271, -0.068), p=0.001), indicating that for every 1-hour increase in sleep duration, LTL decreased by 0.17 kb. RCS analysis showed no evidence of a nonlinear relationship between sleep duration and LTL. After controlling for potential covariates, sleep duration remained negatively associated with LTL (β=-0.123, 95% CI: (-0.229, -0.017), p=0.022). When stratified by sleep quality (moderate or good vs. poor) and age (< 60 vs.≥60 years old), a negative association between sleep duration and LTL was particularly observed among individuals with moderate or good sleep quality and who were under 60 years old.ConclusionThis study adds to the growing literature relating sleep duration with biomarkers of aging and suggests that the shortening of LTL may reflect potential mechanisms through which longer sleep duration contributes to pathological conditions in T2DM patients. It is recommended that healthcare providers, health promoters, and patients pay greater attention to sleep habits, avoiding excessively long sleep durations, to potentially slow cellular aging.